Enteric parasitology. Interpreting laboratory reports. - MacPherson, D. W. (College of Family Physicians of Canada, 1995)
Intestinal parasites are common in the stools of human beings. With care and due attention to the techniques of testing, they are relatively easy to find. Unfortunately, deciding on the clinical importance of stool findings is often difficult. This article is an introduction and guide to interpreting enteric parasitology laboratory reports.